Transient corundum stability in high-temperature metamorphic mineral assemblages: insights from the British Paleogene Igneous Province - O’Driscoll, Brian; Henry, Hadrien (Frontiers in Earth Science, 2025)
Samples containing corundum-anorthite-hercynite are examined to better understand the crystallisation history of this assemblage. These minerals are commonly observed together in the products of high temperature (pyro-)metamorphism of aluminous protoliths. However, it is not clear if they are an equilibrium paragenesis and, if not, whether there is a consistent relative order of crystallisation of the minerals. The physical state of the medium crystallising these phases is also not well understood, with suggested possibilities including crystallisation in the solid state, in refractory Al-rich melts and in systems undergoing melt-rock reaction. Here we investigate the microstructure of the corundum-anorthite-hercynite assemblage in a well-known example from the Loch Scridain Sill Complex (Isle of Mull; ∼60 Ma British Paleogene Igneous Province, NW Scotland), where the rocks of interest comprise crustal xenoliths in a basaltic sill. Another less well-known occurrence from Ardnamurchan, where magmatism is also associated with the British Paleogene Igneous Province, is investigated too. Our combined mineral chemical and electron backscatter diffraction dataset reveal that corundum is a transient phase in both lithologies. The Ardnamurchan rocks comprise discrete oxide (hercynite)- and plagioclase-rich portions, and exhibit macro- and microstructural features interpreted here as forming in a crystal mush, possibly following crystallisation from two immiscible (relatively Fe- and Si-rich) liquids. There is a close crystallographic relationship between corundum and ilmenite in these rocks, with the latter replacing the former in the interstitial spaces between hercynite crystals in the oxide-rich portions of the sample. Corundum in the Mull xenolithic samples exhibits a distinctive texture where hercynite pseudomorphs dendritic and skeletal crystals of the former without apparent changes in the volume or shape of the crystals. This reaction is attributed to infiltration of melt into the xenolith, with consequent conversion of corundum to hercynite. However, the corundum crystal habits and the coarse-grained oikocrystic plagioclase in which they occur are suggestive of crystallisation from an original refractory Al-rich melt phase. Comparisons of the textures observed here with corundum-anorthite-spinel from other settings, including in Archean anorthosites and in corundum-magnetite rocks (emery), suggest that replacement of corundum by spinel may be a ubiquitous process in these rocks.